Environmental correlates of anuran beta diversity in the Brazilian Cerrado. Issue 6 (10th December 2012) - Valdujo, Paula H.; Carnaval, Ana Carolina O. Q.; Graham, Catherine H.
<x xml:space="preserve">Abstract</x> Evolutionary processes are known to influence contemporary patterns of biological diversity, yet disentangling the effects of current and historical drivers of biodiversity patterns remain challenging. We use spatial analyses of community dissimilarity to generate hypotheses about the current and historical processes underlying patterns of beta diversity in anuran species in the Brazilian Cerrado. Specifically, we use a generalized dissimilarity modeling (GDM) approach to model compositional dissimilarity of anuran species and endemics as a function of geographic separation and local (within‐Cerrado) environmental conditions. To gain insight about potential historical processes, we incorporate information from biomes adjacent to the Cerrado to investigate whether environmental conditions in neighboring areas can help explain patterns of beta diversity within the Cerrado. Patterns of anuran beta diversity of both endemics and all species in the Cerrado appear to be strongly influenced by local environmental gradients, with elevation as one of the most important variables in all models. However, in models using endemic species only, environmental conditions of adjacent biomes were related to beta‐diversity patterns, and more strongly so, than to total species models. These results suggest that phylogenetic niche conservatism within species groups that invaded the Cerrado from adjacent biomes may cause these species to be restricted to environmental conditions within the Cerrado that are most similar to the conditions in the adjacent biome where they originated. Time‐calibrated phylogenies of Cerrado endemics and studies of ancestral and current ranges of Cerrado species are needed to test this hypothesis.